Trains, Windmills and Sand: An entry to the Arizona Historical Society Museum Competition - Bob Burnham; Raymond Streeter (Oz, 1986)
In 1985, the Arizona Historical Society sponsored a competition for the design of a museum to be constructed on a site in Tempe adjacent to Phoenix's Papago Park. This facility is intended to house the Society's collections documenting and illustrating the Hispanic and Anglo/Hispanic periods in Arizona history...